Respiratory health among workers at bakery company - Nur Fatihah, Mohd Ghani (2015)
This study explained about the respiratory health among workers that working at bakery industry. Bakery is a small-scaled industry in Malaysia and not all respiratory health problems among workers that exposed to a variety of dusts in industries and generate dust during their production process have been well-documented. Bakeries can be highly contributed to many lung diseases as the working environment is mostly exposed to flour dust concentration. The objective of this study is to measure level of respiratory health problems among workers at bakery. A set of questionnaire about the demographic information and 12 respiratory symptoms were being distributed among 31 bakery workers. Then, spirometer was used in order to measure the level of lung function among them. A personal air sampling pump was used to measure the exposure of concentration PM25 The data collected then has been statistically test by using simple linear regression, bivariate correlation and also multiple linear regressions. From the result, it is observed that all of the workers are having respiratory symptoms. Spirometric results showed that 84% of the workers were having abnormal lung function (obstructive and restrictive). Personal air monitoring showed the highest concentration PM2.5 exposed by a worker is 2.2 Mg/M3, which higher than permissible exposure limit. The results demonstrated the total of symptoms experienced by a worker, lung function level and exposure of concentration PM 2.5 from different activities at the bakery. It is proven that workers that working at bakery sector has respiratory health problem due to exposure of flour dust.